Harm reduction workers and the challenge of engaging couples who inject drugs in hepatitis C prevention. (1st November 2016) - Treloar, Carla; Rance, Jake; Bryant, Joanne; Fraser, Suzanne
Highlights: Harm reduction for hepatitis C is typically focused on individuals who inject drugs. Couples who inject could be more effectively involved in hepatitis C harm reduction. Harm reduction workers need additional support to work with couples. The strengths of relationships could be mobilised for hepatitis C harm reduction. Abstract: Aims: Despite injecting-equipment sharing between sexual partners leaving them at increased risk of hepatitis C (HCV), there is scant literature available to guide harm reduction workers in their encounters with couples who inject drugs. This article explored workers' understandings of such couples and their accounts of working with them in relation to HCV prevention. Method: Semi-structured interviews were conducted with 22 staff of harm reduction services located in Sydney and Melbourne, Australia. Results: Overall, staff represented couples as either absent from the service or as presenting with needs indiscernible from those of individual clients. Responses to questions about HCV and couples were framed primarily in terms of risk. Staff participants questioned 'genuineness' of clients' intimate relationships, instead characterising them as inauthentic and drug-driven. Working with couples was seen to present a number of organisational and clinical challenges. The benefits of recognising and working with such partnerships received scant acknowledgement. Rather, staff tended to perceive couples as being 'impenetrable' to health promotion messaging. Discussion: The framing and delivery of harm reduction in Australia remains an individualising enterprise with little capacity to recognise the intimate partnerships, including addressing the HCV risks specific to them. More effective harm reduction strategies may be achieved by transitioning to a practice framework that addresses the social context of injecting, including the experience of couples. This would require direct involvement of couples who inject drugs.